Electrical modeling of the GaAs/InP wafer bonded heterojunction. Issue 2 (23rd January 2014) - Blot, Xavier; Scheiblin, Pascal; Moriceau, Hubert; Daele, William Van Den; Lecouvey, Christophe; Delprat, Daniel; Tauzin, Aurélie; Drazek, Charlotte; Guiot, Eric
Abstract The electrical behavior of wafer bonded heterojunctions is usually modeled with the assumption of a pure thermionic conduction at the interface. In this paper, we study the case of highly doped bonded wafers using a Technology Computer Aided Designed (TCAD) modeling approach. Several plausible options of interface including fixed surface charges, interface states densities or a defective interface layer, are discussed and compared with current‐voltage measurements. Considering both thermionic and tunnel transport through the interface, we show how the ratio of the competing transport mechanisms depends on the shape of the interfacial energy barrier. Finally, the simulation accurately predicts the effect of the operating temperature on current‐voltage characteristics, thanks to a process‐compliant description of the direct bonded heterojunction. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)